(untitled) (Biological Sciences - PJSIR, 2025)
Background: The study aimed to investigate antinuclear antibodies (ANA) and anti-double- stranded DNA antibodies among healthy individuals in Rawalpindi and Islamabad, emphasizing the need to understand their prevalence in the general population. Objective: To determine ANA and anti-dsDNA levels, assessing their potential as disease biomarkers in the absence of clinical symptoms among healthy individuals. Methods: A total of 659 individuals participated in the study, including 503 females (76.3%) and 156 males (23.5%). Blood samples were collected using convenient sampling technique followed by separation of serum using centrifugation. The levels of ANA and anti-dsDNA were quantified using non-competitive ELISA. Results: The results of the study showed that only 0.91% of individuals tested positive for ANA and 0.46% for anti-dsDNA. This indicates a minimal presence of these antibodies in the healthy cohort. Furthermore, no significant association was found between ANA and anti-dsDNA. Conclusion: This study highlights a low occurrence of ANA and anti-dsDNA among healthy subjects, suggesting their potential exclusive association with autoimmune diseases.